PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS V SDN DURI KEPA 13 - Nur Agustina; Harlinda Syofyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study is classroom action research (PTK) with the aim of improving learning outcomes in science subjects with the material "Animal and Human Movement Organs" through the application of the Make a Match learning model to class V students at SDN Duri Kepa 13. The research involved 27 students from class V D, which consists of 12 male students and 15 female students. The research was carried out in two cycles, with each cycle consisting of two meetings involving four research stages, namely planning, implementing actions, observing and reflecting. Data was obtained through observation and tests. Data analysis was carried out in a comparative descriptive manner by comparing the results between the two cycles. The research results showed that: (1) there was an increase in student activity in the Make a Match model learning, with the average percentage of student activity increasing from 75% in cycle I to 90% in cycle II; (2) there was an increase in the average value of student learning outcomes and the percentage of completeness of student learning outcomes, with the average value increasing from 62.28 in cycle I to 76.36 in cycle II, and (3) the percentage of completeness of student learning outcomes increased from 60% in cycle I to 88% in cycle II. Based on these findings, it can be concluded that the use of the Make a Match learning model is effective in improving student learning outcomes in science subjects with the material "Animal and Human Movement Organs" in class V.